Towards identifying and ranking selected types of violence against women in North India - Singh, Raghu N. (International journal of comparative and applied criminal justice, 2017)
The paper is aimed at identifying and ranking different types of violence against women (VAW) in states of Delhi and Haryana in Northern India. Examples of gender-specific violence were selected through an extensive review of the literature. The types of VAW reviewed include the lower economic value of daughters at birth (females being considered a liability rather than an asset), rampant female feticides aided by proliferation of often illegal prenatal diagnoses, maternal morbidity, and mortality rates, physical and emotional abuse and neglect of female children, “honour” killing of women, exclusion and deprivation of women from medical treatment and nutrition, their subjection to assaults and rape (including marital rape), insufficient compliance to women’s legal rights of inheritance, arranging early marriages of girls, dowry deaths, female sexual harassment, and intimidation in community and workplace, female trafficking and prostitution, and so forth.The conceptual frame of reference used for the study was provided by the culturally sanctioned legitimation of the patriarchal system of Indian family as well as by people’s perceptions and attitudes. Data were collected through the survey method in two phases. A preliminary survey was conducted during the first phase for developing the questionnaire items to be used for data collection in the phase two of the study. The findings of the study are presented and reveal participants’ rankings of selected types of VAW by degree of relative importance. Data, based on secondary sources as well as a non-random sample of respondents, were analysed to assess the various areas which demand immediate redress. We also interpret data based on selected criteria and suggest few optimistic future trends in regard to addressing and preventing VAW.